A pilot study to compare footwork techniques used in table tennis - Malagoli Lanzoni, I.; Lobietti, R. (World Congress of Performance Analysis of Sport VIII, 2008)
The basic assumption for this pilot study is the necessity to deepen one of the most important aspects for the advancing of table tennis: footwork techniques. To reach this goal it`s been necessary to use a standard classification of the steps that can represent a technical shared benchmark suitable for forthcoming studies. The analysis so far are based on the comparison between the two chosen technical levels and can be used to get an optimal technical remark of international level. In particular each coach, technician and national trainer can obtain important news and hints from this kind of analysis in order to improve their work especially with beginner players. This kind of analysis can be used from a technical point of view by each player to study his/her strong and weak points and to improve his/her training. In the case of yet technically formed players it`s really useful to know the footwork technique in order to refine his/her abilities and to get better agonistic results. Again another use of this study is represented by the tactical use that can be displayed starting from a deep knowledge of footwork. Knowing one`s values and one`s faults in performing the movements is important to meliorate one`s technique, but it`s even more important to know values and faults of the challenger from the tactical point of view in order to get better agonistic results.